2008
DOI: 10.1097/tp.0b013e3181908f60
|View full text |Cite
|
Sign up to set email alerts
|

Hurdles, Barriers, and Successes of a National Living Donor Kidney Exchange Program

Abstract: A living donor kidney exchange program is a dynamic process. Many clinical hurdles and barriers are encountered that for a large part were not foreseen but should be taken into account when programs are initiated based on computer simulations. Success is dependent on a flexible organization able to create alternative solutions when problems arise. Centralized allocation and crossmatch procedures are instrumental in this respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 9 publications
2
42
0
Order By: Relevance
“…In a simulated model using United Network for Organ Sharing (UNOS) data, Gentry et al estimated that 60 % of KPD candidates are blood group O, whereas only 30 % of donors in such pools are blood group O [19]. Others have reported similar results; for example, in the Dutch KPD programme, around 67 % of ABOi pairs were found to have type O recipients, whereas only about 30 % of pairs have type O donors [20]. In traditional KPD pools of incompatible pairs, match rates for type O recipients with non-type O donors are around 15 %, whereas rates for other pairs with donors of other blood group types are close to 50 % [21].…”
Section: Altruistic Unbalanced Paired Kidney Exchange (Aupke)supporting
confidence: 54%
See 1 more Smart Citation
“…In a simulated model using United Network for Organ Sharing (UNOS) data, Gentry et al estimated that 60 % of KPD candidates are blood group O, whereas only 30 % of donors in such pools are blood group O [19]. Others have reported similar results; for example, in the Dutch KPD programme, around 67 % of ABOi pairs were found to have type O recipients, whereas only about 30 % of pairs have type O donors [20]. In traditional KPD pools of incompatible pairs, match rates for type O recipients with non-type O donors are around 15 %, whereas rates for other pairs with donors of other blood group types are close to 50 % [21].…”
Section: Altruistic Unbalanced Paired Kidney Exchange (Aupke)supporting
confidence: 54%
“…They also found that individual centres were pursing desensitization therapy separate from the KPD programme for enrolled patients from their respective centres [34]. This is in contrast to the Dutch and South Korean models, where blood group identical exchanges are prioritized in order to maximize transplant rates for patients with blood group O [20,35]; an exception to this rule was in place for highly sensitized non O recipients, who may otherwise not find a cross-match negative donor.…”
Section: Uk National Programmementioning
confidence: 73%
“…However, considerable controversy remains regarding the best practices for accomplishing this goal (15)(16)(17)22,23). This report demonstrates that virtual crossmatches can be used to reliably predict acceptable cell-based crossmatches and a large number of transplants can be achieved by allowing each transplant center to establish criteria for assigning unacceptable antigens and acceptable crossmatches.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, this high rate of accurate virtual crossmatches was achieved without conservative strategies that have been proposed by others, such as establishing common parameters for unacceptable antigens and acceptable crossmatches or employing a central laboratory (15,16).…”
Section: Successful Virtual Crossmatching For Kpdmentioning
confidence: 99%
See 1 more Smart Citation